Thermo-optic refraction based switchable optical mode converter. (November 2021) - Shetty, Pritam P; Maksimov, Dmitrii N; Babu, Mahalingam; Bongu, Sudhakara Reddy; Bingi, Jayachandra
Highlights: Demonstration of optically switchable mode converter. Cross phase modulation effect on Laguerre Gaussian(LG) beam in 2D MoS2 medium is studied. Topological charge and helicity of Laguerre Gaussian beam can be easily measured using this switchable mode converter. Theoretical analysis proved mode transformation is a result of Fourier components of LG beam undergoing different phase shifts. Abstract: The temporally switchable optical mode conversion is crucial for optical communication and computing applications. This research demonstrates such optically switchable mode converter driven by thermo-optic refraction. The MoS2 nanofluid is used as a medium where the thermal microlens is created by a focused laser beam (pump). The convective thermal plume generated above the focal point of the pump beam within the nanofluid acts as an astigmatic thermal lens. It is discovered that mode conversion of the Laguerre-Gaussian (LG) to the Hermite-Gaussian (HG) beam (vice versa) takes place upon passing through the thermal lens. The topological charge of the LG beam can be easily determined using the proposed mode converter. The mode transformation is explained theoretically as the Fourier components of the LG beam undergoing different optical paths while propagating through the convective plume.